Antimicrobial stewardship programs: methods of operation and suggested outcomes. Issue 1 (January 2012) - Griffith, Milena; Postelnick, Michael; Scheetz, Marc
The judicious use of antibiotics is an important strategy to preserving efficacy in the treatment of infectious diseases. Infectious disease practitioners are poised to provide patient-specific recommendations for appropriate agents and to optimize dosage and duration of therapy. Antimicrobial stewardship programs (involving pharmacists, physicians and other healthcare providers) are increasing in number as antibiotic resistance increases with a disproportionately small number of new agents being developed. Two strategies for antimicrobial stewardship are currently endorsed by national organizations and include preauthorization/formulary restriction and prospective audit with feedback. As it is important for programs to choose appropriate clinical and financial outcomes goals in order to assure sustainability, we review these strategies and discuss the impact of each on clinical outcomes and costs.